ENGLISH-MEDIATED DIGITAL TOUR GUIDING IN VIRTUAL TOURISM USING LINGUISTIC AND AUDIOVISUAL STRATEGIES - I Nengah Laba; I Wayan Budiarta; Sunitha Venugopal (Universitas Warmadewa, 2026)
This study explores the use of English in digital tour guiding by analyzing five YouTube videos that represent virtual tourism practices. The research aims to identify the linguistic, narrative, and technological strategies employed by guides in delivering online tour experiences. Using a qualitative descriptive approach and content analysis, the study examines how guides adapt their communication to suit international audiences in digitally mediated environments. The findings reveal that guides rely on simplified language, controlled pacing, and descriptive explanations to enhance comprehensibility. Audiovisual techniques such as camera movement, framing, and zooming play a crucial role in replacing physical gestures and supporting meaning-making. The study demonstrates that effective digital tour guiding requires the integration of English-mediated communication, cultural interpretation, and technological competence. These findings highlight the evolving nature of tour guiding in the digital era and emphasize the importance of multimodal communication in shaping virtual tourism experiences.